The Position of Ijbar Rights in Perspective Islamic Law and Human Rights - Munir, Misbachul; Zumrotun, Siti (El-Usrah: Jurnal Hukum Keluarga, 2023)
This article aims to illustrate the concept of ijbar according to Islamic religious law based on the opinion of jurists about the right to force a girl (ijbar right) to marry owned by her guardian even without her consent because a guardian is considered to be the one who knows best about what is best because women are considered not proficient in formulating things that are best for her,  Therefore, consent is not a priority that ultimately monopolizes women's interests and has the potential to cause violence against women, therefore this article tries to describe ijbar rights according to the perspective of Islamic Law and Human Rights.